Dr. Darin Muangthai — Deep Plane Facelift — Bangkok - Muangthai, Darin (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Darin Muangthai, practicing in Bangkok, Thailand. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003124; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; thailand; bangkok